Literature Review: EFEKTIVITAS PENGGUNAAN GAME EDUKATIF DALAM MENINGKATKAN KETERAMPILAN MENULIS DI SEKOLAH DASAR - Maulidya Yasmin; Dinda Siti Hawa; Ichsan Fauzi Rahman , (Jurnal Penelitian Pendidikan Indonesia (JPPI), 2025)
This study examines the effectiveness of educational games and language-based game methods inenhancing writing skills, literacy, numeracy, and character development among elementary schoolstudents through a literature review approach. The findings indicate that game-based learningmedia such as games, puzzles, Wordwall, and Android-based applications significantly improvestudents' motivation, active engagement, collaboration, and learning outcomes. Interactiveactivities such as sentence construction, story completion, and creating digital comics have beenproven to help students develop ideas, enrich vocabulary, enhance language accuracy, and build selfconfidence in written communication. Despite challenges such as limited access to technology andlack of teacher understanding, with proper design and implementation, educational games havegreat potential to improve the quality of writing instruction and support holistic characterdevelopment. These findings are expected to serve as a foundation for teachers and policymakers inmore widely and effectively integrating educational games into the elementary educationcurriculum in Indonesia